1964
DOI: 10.2466/pr0.1964.15.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Contagion

Abstract: 4 separate experiments on the contagion of game-playing behavior were conducted. Exp. I indicated that contagion occurred whether the game engaged in by the confederate was of high or low valence to S, that mere activity on the part of the experimental confederate did not lead to game playing, and that contagion tended toward specificity. Exp. II indicated specificity of contagion was not necessary, that contagion was not entirely due to a desire to compere in game playing. Exp. III failed to produce contagion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…We distinguish social contagion from social facilitation, which is concerned merely with the presence of conspecifics rather than conspecifics engaged in the same behavior as the recipient [Epple & Alveario, 1985;Gochfeld, 1978;Guerin & Innes, 1984;Stamm, 1961;Straumann & Anderson, 1991;Zajonc, 1965]. Behavioral social contagion has been demonstrated for humans [Jones, 1998;Polansky et al, 1950;Rodgers & Rowe, 1993;Wheeler, 1966Wheeler, , 1968Wheeler et al, 1964] and for a number of other species and behaviors, including feeding behavior in puppies, pigs, ponies, cows, chickens, and other birds [Benham, 1982;Birke, 1974;Evans & Marler, 1994;Grosser et al, 1951;James, 1953;Keeling & Hurnik, 1993;Kilgour, 1978;Sweeting et al, 1985;Tolman, 1967aTolman, , b, 1968Tolman & Wilson, 1965;Turner, 1964]; preening behavior in birds [Birke, 1974;Palestis & Burger, 1998]; nest building in birds [Birke, 1974;Bruen & Dunham, 1973]; and running speed in dogs [Scott & McRay, 1967]. Studies of behavioral contagion (also called the ''neighbor effect'') [Baker & Aureli, 1996] in primates have focused primarily on agonistic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…We distinguish social contagion from social facilitation, which is concerned merely with the presence of conspecifics rather than conspecifics engaged in the same behavior as the recipient [Epple & Alveario, 1985;Gochfeld, 1978;Guerin & Innes, 1984;Stamm, 1961;Straumann & Anderson, 1991;Zajonc, 1965]. Behavioral social contagion has been demonstrated for humans [Jones, 1998;Polansky et al, 1950;Rodgers & Rowe, 1993;Wheeler, 1966Wheeler, , 1968Wheeler et al, 1964] and for a number of other species and behaviors, including feeding behavior in puppies, pigs, ponies, cows, chickens, and other birds [Benham, 1982;Birke, 1974;Evans & Marler, 1994;Grosser et al, 1951;James, 1953;Keeling & Hurnik, 1993;Kilgour, 1978;Sweeting et al, 1985;Tolman, 1967aTolman, , b, 1968Tolman & Wilson, 1965;Turner, 1964]; preening behavior in birds [Birke, 1974;Palestis & Burger, 1998]; nest building in birds [Birke, 1974;Bruen & Dunham, 1973]; and running speed in dogs [Scott & McRay, 1967]. Studies of behavioral contagion (also called the ''neighbor effect'') [Baker & Aureli, 1996] in primates have focused primarily on agonistic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…s More recently, Baron and Kepner (1970) reported imitation of nonaggressive as well as of aggressive models. Wheeler (1966Wheeler ( , 1968 has also shown that a person's responses in a situation of conflict over aggressing can be influenced by observation of another's response in a similar situation. In the present study, we were concerned with the possibility that disobedience to a command to aggress may also be imitated.…”
mentioning
confidence: 99%
“…The true Ss made their judgments over a microphone. This basic group influence technique, though n?t directly studied, has since been adapted by Wheeler, Smith, & Murphy (1964) primarily to create experimental deception.…”
Section: Methodsmentioning
confidence: 99%